2011
DOI: 10.1002/hep.24239
|View full text |Cite
|
Sign up to set email alerts
|

Ron receptor regulates Kupffer cell-dependent cytokine production and hepatocyte survival following endotoxin exposure in mice

Abstract: Previous studies demonstrated that targeted deletion of the Ron receptor tyrosine kinase (TK) domain in mice leads to marked hepatocyte protection in a well-characterized model of lipopolysaccharide (LPS)-induced acute liver failure in D-galactosamine (GalN)-sensitized mice. Hepatocyte protection in TK2/2 mice was observed despite paradoxically elevated serum levels of tumor necrosis factor alpha (TNF-a). To understand the role of Ron in the liver, purified populations of Kupffer cells and hepatocytes from wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 29 publications
4
72
0
Order By: Relevance
“…It is possible that those contradictory results are due to different target cells in the liver. This view is supported by a follow-up study by Stuart et al, which used Kupffer cells and hepatocytes from RON TK À/À mice and demonstrated that RON TK À/À Kupffer cells treated with LPS lead to remarkable up-regulation of serum TNF-a level, whereas RON TK À/À hepatocytes exhibited an increased resistance to inflammatory factors and cell death in comparison with normal genotypic hepatocytes [2]. Mechanisms behind the opposing MSP effects in hepatocytes and Kupffer cells are not clarified yet, however, it was suggested that the hepatocyte-protective effect may come from the early increase of TNF-a, since the TNF-a increase in early stage actually could be beneficial to hepatocytes [52].…”
Section: Msp Regulates Inflammatory Processes In Vivomentioning
confidence: 76%
See 2 more Smart Citations
“…It is possible that those contradictory results are due to different target cells in the liver. This view is supported by a follow-up study by Stuart et al, which used Kupffer cells and hepatocytes from RON TK À/À mice and demonstrated that RON TK À/À Kupffer cells treated with LPS lead to remarkable up-regulation of serum TNF-a level, whereas RON TK À/À hepatocytes exhibited an increased resistance to inflammatory factors and cell death in comparison with normal genotypic hepatocytes [2]. Mechanisms behind the opposing MSP effects in hepatocytes and Kupffer cells are not clarified yet, however, it was suggested that the hepatocyte-protective effect may come from the early increase of TNF-a, since the TNF-a increase in early stage actually could be beneficial to hepatocytes [52].…”
Section: Msp Regulates Inflammatory Processes In Vivomentioning
confidence: 76%
“…RON À/À mice with LPS-induced acute endotoxemia exhibited lowered anti-inflammatory cytokine-interleukin 10 (IL-10) mRNA expression in the liver compared with wild-type mice, accompanied with deceased level of superoxide dismutase (SOD), an important antioxidant enzyme that works against oxidative stress in liver [50]. To block the intracellular signaling of MSP-RON, mice with deletion of tyrosine kinase domain of RON (RON TK À/À mice) were used in several studies [2,51,52]. In a model of acute liver failure, it was shown that RON TK À/À mice were more prone to severe inflammation showing an increased TNF-a level and a decreased IL-10 level in serum, in response to LPS and galactosamine (GalN).…”
Section: Msp Regulates Inflammatory Processes In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Also, RON has been shown to be overexpressed at mRNA and protein levels in HCC (28). Various cytokines including hepatocyte growth factor, TNF-α, IL-1 and IL-6 increase RON expression in lipopolysaccharideinduced murine model of acute liver failure and HCC cell line (28)(29)(30). Therefore, induction of RON by these cytokines may play an important role in development and progression of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…qRT-PCR was performed using an ABI7900HT (Applied Biosystems by Life Technologies, Carlsbad, CA) as previously described (19,22). Briefly, independent mammary gland or tumor RNA preparations from six mice of each genotype were made at the time points indicated.…”
Section: Quantitative Real-time (Qrt)-pcrmentioning
confidence: 99%